Variaciones anatómicas del proceso uncinado en tomografía computada multidetector en pacientes con rinosinusitis crónica (2014)
Objective To describe the uncinate process anatomy and its variations observed through coronal, multislice computed tomography (MSCT) in patients with chronic rhinosinusitis. Introduction As reviewed in the literature, no studies of anatomical variations ostiomeatal complex in Colombian adults were found. The reports agree that the anatomical variations of this complex are part of the causes of chronic sinusitis refractory to medical treatment, which motivated the present work to study the anatomy of this complex and identify possible anatomic variations in adult patients from Colombia, diagnosed with chronic sinusitis. Materials and methods A descriptive, cross-sectional, observational and retrospective study. Continuous variables were estimated with measures of central tendency and dispersion, with a confidence interval of 95%. Categorical variables were determined with frequencies and percentages. Results The total sample was 143 cases. In the sample, 53.8% were men and 46.2% were women. Both of the right and left, the uncinate process of the ethmoid was inserted into the lamina papyracea in 49.7% and 53.1% of cases, respectively. The insertion of the uncinate process in the cribriform plate of the ethmoid (T6) had a frequency to the right side of 25.2%, but for the left side was the insertion into the middle nasal concha (T1) (23.8%). In most cases, the uncinate process had a lateral orientation and 51% on the right side and 56.6% on the left side. Conclusion The uncinate process is a highly variable anatomical structure at each side of the nasal cavity, arranged in different insertion sites, changes in angle and different lengths which is important from the point of view of surgical management of chronic rinosinusitis. © 2013 Sociedad Argentina de Radiología. Published by Elsevier España, S.L. All rights reserved.